2017
DOI: 10.1021/jacs.7b08710
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Delivery of Aggregation-Induced Emission Nanoparticles and Pure Organic Phosphorescent Nanocrystals by Saponin Encapsulation

Abstract: Saponins are a class of naturally occurring bioactive and biocompatible amphiphilic glycosides produced by plants. Some saponins, such as α-hederin, exhibit unique cell membrane interactions. At concentrations above their critical micelle concentration, they will interact and aggregate with membrane cholesterol to form transient pores in the cell membrane. In this project, we utilized the unique permeabilization and amphiphilic properties of saponins for the intracellular delivery of deep-red-emitting aggregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(82 citation statements)
references
References 49 publications
(90 reference statements)
1
81
0
Order By: Relevance
“…Cell nucleus colocalization experiments also prove the phenomenon in which the SiCNs show well‐fitting patterns with the nucleus of the cells (Figure S14, Supporting Information) . It is reported that saponins existed in notoginseng could interact with membrane components (like phospholipids and cholesterol), thus forming transient pores in the membrane . In addition, the notoginseng‐conjugated SiCNs have small enough particle size (≈2.1 nm).…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…Cell nucleus colocalization experiments also prove the phenomenon in which the SiCNs show well‐fitting patterns with the nucleus of the cells (Figure S14, Supporting Information) . It is reported that saponins existed in notoginseng could interact with membrane components (like phospholipids and cholesterol), thus forming transient pores in the membrane . In addition, the notoginseng‐conjugated SiCNs have small enough particle size (≈2.1 nm).…”
Section: Resultssupporting
confidence: 57%
“…[36] It is reported that saponins existed in notoginseng could interact with membrane components (like phospholipids and cholesterol), thus forming transient pores in the membrane. [1] In addition, the notoginseng-conjugated SiCNs have small enough particle size (≈2.1 nm). Therefore, such resultant SiCNs might enter the nucleus through stepping across the transient nuclear membrane pores due to their pore forming property and small size.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tang and co‐workers also reported that compound 15 BDBF with a lifetime of 0.23 s and emission efficiency of 36% under ambient conditions has the potential to be the candidate of bioimaging agents in 2017. However, pure 15 nanocrystals are unable to enter cells.…”
Section: Rtp Materials In Biomedical Applicationsmentioning
confidence: 99%
“…Recently,p ure organic luminogens with room-temperature phosphorescence (RTP) [1][2][3][4] have attracted increasing attention owing to their fundamentali mportance in deciphering the photophysical processes of singleta nd triplet excitons, [5][6][7][8][9][10] as well as their potentiala pplications in sensing, [5,[11][12][13] bioimaging, [14][15][16] anticounterfeiting, [8,[17][18][19] and so forth. In particular, those with persistent RTP (p-RTP) are also promising owing to the retaining of RTP emissione ven after ceasing the excitation sources, which means they can be used in encryption, oxygen and chemical sensing, and high-resolution molecular imaging with ideal signal-to-noise ratios.…”
Section: Introductionmentioning
confidence: 99%